Preparation course for the toefl test practice test - Phillips, Deborah; Lê Huy Lâm (Tp.HCM : Nxb Tp.HCM, 2000)
This book is intended to prepare students for the toefl test, be used in a variety of ways, depending on the needs of the readers.
Keywords: Toefl; Practice tests; English language